2013
DOI: 10.1038/sc.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intramedullary stress on cervical spondylotic myelopathy

Abstract: Study design: A cross-sectional analysis. Objective: To examine whether intramedullary stress is related to the appearance of symptoms in cervical spondylotic myelopathy (CSM). Setting: Japan. Methods: Thirty-three consecutive patients with CSM and 30 consecutive patients without CSM were enrolled. A total of 99 disc levels from C3 to C6 in 33 patients with CSM were divided into two groups: 33 disc levels with high signal intensity (HSI) on T2-weighted magnetic resonance image (HSI group) and 66 disc levels wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…CSM is the predominant reason of spinal cord injury and neurological dysfunction especially among industrialized countries, which may lead to disability as a life-long event, posing a great social and economic burden [ 4 , 5 ]. It has been highlighted that the compromise of spinal canal as well as the compression of spinal cord were the main pathology of CSM, and the etiology of CSM was suggested to be the age-related degenerative spondylosis [ 6 , 7 ]. At present, patients diagnosed with symptomatic CSM were often recommended to receive anterior cervical decompression and fusion for patients diagnosed with CSM [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CSM is the predominant reason of spinal cord injury and neurological dysfunction especially among industrialized countries, which may lead to disability as a life-long event, posing a great social and economic burden [ 4 , 5 ]. It has been highlighted that the compromise of spinal canal as well as the compression of spinal cord were the main pathology of CSM, and the etiology of CSM was suggested to be the age-related degenerative spondylosis [ 6 , 7 ]. At present, patients diagnosed with symptomatic CSM were often recommended to receive anterior cervical decompression and fusion for patients diagnosed with CSM [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…25 30 Takahashi et al reported on the relationship between high signal intensity on MRI and FEM model. 31 The above papers evaluated the stress distribution and thus provide valuable background information for understanding the injury mechanism of spinal cord. However, the pathology of the gray matter and white matter that caused the symptoms was not evaluated.…”
Section: -19mentioning
confidence: 99%
“…Theoretically, lumbar dynamic stability system reduces adjacent segment degeneration and the stress on the intervertebral bone graft and promotes bone healing and spine recovery. However, high-level stress will cause spinal cord compression and induce nerve tissue damage [ 31 ]. Lumbar Ti-24Nb-4Zr-8Sn fixation system is a dynamic stability system made of titanium alloy and polyether ether ketone (PEEK) materials [ 32 ].…”
Section: Discussionmentioning
confidence: 99%